Spinoza’s Strong Eudaimonism - Brandon Smith (Journal of Modern Philosophy)
In this paper I defend an eudaimonistic reading of Spinoza’s ethical philosophy. Eudaimonism refers to the mainstream ethical tradition of the ancient Greeks, which considers happiness a naturalistic, stable, and exclusively intrinsic good. Within this tradition, we can also draw a distinction between weak eudaimonists and strong eudaimonists. Weak eudaimonists do not ground their ethical conceptions of happiness in complete theories of metaphysics, epistemology, or psychology. Strong eudaimonists, conversely, build their conceptions of happiness around an overall philosophical system that extends far beyond ethics, while nevertheless being directed at the promotion of a happy life. I will show that Spinozistic happiness is not only naturalistic, stable, and exclusively intrinsically good, but that Spinoza is also a strong eudaimonist because his ethical account of happiness is incomprehensible without appeal to metaphysical, epistemological, and psychological doctrines. As well, I will explain how the apparent subjective and relativistic features of Spinoza’s ethics do not undermine the eudaimonistic reading, because both Spinoza and the ancient eudaimonists grant that the beliefs/feelings of the subject play a necessary (but insufficient) role in happiness as the highest good.